A study on the impact of external debt on economic growth during economic crises - Chua, Hans N.; Monteverde, Redwin Griffith N.
This study investigates the relationship between external debt and economic growth during both crisis and non-crisis periods. In the 2007 to 2009 Global Financial Crisis, the housing bubble in the US burst leading to the collapse of the financial system in the US and consequently causing a global economic recession. The purpose of the study is to observe the effectiveness of a country’s decision to incur external debt as a tool to counter the economic shock brought about by the Global Financial Crisis. This is done with the use of a panel regression analysis to test Fosu’s [1999] Direct Effect of Debt Hypothesis. The panel regression model in this study is based on Fosu’s [1996] augmented production function, which posits economic growth being a function of capital growth, export growth, and labor force growth. The sample of the countries and the data used in this study span from 2002 to 2014. The countries in the sample are those that had available data and countries that were affected by the 2007 to 2009 Global Financial Crisis. The dependent variable of the panel regression model is GDP growth, which is a proxy for economic growth. The independent variables are capital growth proxied by gross capital accumulation as a percentage of GDP, export growth proxied by the exports of goods and services as a percentage of GDP, labor force growth proxied by the log of the total labor force, the external debt to GDP ratio, the dummy variable that indicates the existence of a crisis, and the interaction term between the external debt to GDP ratio and the dummy variable indicating the existence of a crisis. Other control variables were added into the second model of the panel regression. The results of the models suggest the robustness of Fosu’s [1996] augmented production function. Furthermore, the results suggest that the incurrence of external debt is detrimental to economic growth, and the incurrence of external debt during crisis periods is insignificant in spurring economic growth. The implications made can be used to assess the effectiveness of the incurrence of external debt during economic crises as a result of the recent COVID-19 pandemic.